Poverty and economic dislocation reduce compliance with COVID-19 shelter-in-place protocols - Wright, Austin L.; Sonin, Konstantin; Driscoll, Jesse; Wilson, Jarnickae (Journal of economic behavior & organization, 2020)
Shelter-in-place ordinances were the first wide-spread policy measures aimed to mitigate the spread of COVID-19. Compliance with shelter-in-place directives is individually costly and requires behavioral changes across diverse sub-populations. Leveraging county-day measures on population movement derived from cellphone location data and the staggered introduction of local mandates, we find that economic factors have played an important role in determining the level of compliance with local shelter-in-place ordinances in the US. Specifically, residents of low income areas complied with shelter-in-place ordinances less than their counterparts in areas with stronger economic endowments, even after accounting for potential confounding factors including partisanship, population density, exposure to recent trade disputes, unemployment, and other factors. Novel results on the local impact of the 2020 CARES Act suggest stimulus transfers that addressed economic dislocation caused by the COVID-19 pandemic significantly increased social distancing.